Pengaruh Displin Kerja dan Motivasi terhadap Kinerja Karyawan Dinas Koperasi dan Usaha Mikro Kota Depok - Fachria Fauhatuzzahro; Rani kurniasari (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This research was conducted at the Department of Cooperatives and Micro Enterprises, Depok City. The aim of this research is to determine the level of work discipline, motivation, employee performance and whether there is an influence of work discipline and motivation on employee performance, either partially or simultaneously. The research method used is a quantitative statistical method. The data collection technique used is by distributing questionnaires with data analysis techniques. In the research object, the influence of work discipline and motivation on the performance of employees of the Department of Cooperatives and Micro Enterprises of Depok City. In this study, researchers used a questionnaire that had been distributed to employees of the Department of Cooperatives and Micro Enterprises of Depok City who had filled out the questionnaire/questionnaire. The test stages carried out are: existing instrument test (validity test and reliability test), classical assumption test (normality test, multicollinearity and heteroscedasticity test), multiple linear analysis test. Test the coefficient of determination R2, t test and f test, and with the help of Google form and data that has been proven valid and succeeded in collecting 50 respondents. In partial hypothesis testing, the work discipline variable (X1) has a positive and significant effect on employee performance because the value is 3.807 > 1.676. Apart from that, it is known that the sig value is 0.000, where the sig value. smaller than 0.05 or 0.000 < 0.05 then Ho is rejected and Ha is accepted, meaning that the work environment is significant for employee performance (Y). Motivation (X2) has a significant effect on employee performance because the calculated t value is greater, 3,382 < 1,676. Apart from that, it is known that the sig. equal to 0.616 > 0.05, then Ho is accepted and Ha is rejected, meaning that work motivation has a negative but significant effect on employee performance (Y). Simultaneously testing the hypothesis can be seen that the sig. value for the influence of (X1) and (X2) on (Y) is 0.000 < 0.05 and the Fcount value is 23.935 > 4.03, so it can be concluded that Ho is rejected, Ha is accepted, in the words On the other hand, there is a simultaneous and significant influence of variables (X1) and (X2) on variable (Y). Based on the analysis of respondents' answers, it was concluded that there was an influence of work discipline and motivation on employee performance at the Department of Cooperatives and Micro Enterprises in Depok City, both partially and simultaneously.